The Meaning of and Space for Women Empowerment in the World of Male-Dominated Sports: An Interpretative Phenomenological Analysis - David, Cayenne Gabrielle B. (Animo Repository, 2022)
Women empowerment among athletes has been one of the significant factors in female sports engagement. The objective of this research is to uncover how female athletes who participate in male-dominated sports experience empowerment. The researchers utilized the Snowball technique to interview eight women university athletes with at least one year of experience in the sports of basketball or football for this qualitative study. Topics such as how athletes interpret empowerment and how they experience empowerment on a personal level were covered in semi-structured interviews. To assess the data, they analyzed through IPA techniques. According to the findings, women athletes define empowerment as a resource that allows them to create and improve their self-confidence and motivation. They also consider it as a means of boosting their self-esteem and motivation through athletics. Women athletes receive personal and collective empowerment as a result of their encounters of being confident. Based on data, self-worth, opportunities, and confidence fuel women athletes' empowerment. Yet, there are factors that make it difficult, such as prejudice or unfair treatment. Further, sports can also contribute to other aspects of empowerment such as social connection and ability to influence.